Development of arduino basic learning kit in robotics for beginner level learning - Lim, Tan Kooi; Mohammad, Ahmad Zumali; Ismail, Mohd Noor Bin (Universitas Negeri Padang, 2021)
This Basic Arduino Learning Kit in Robotics is developed to help someone who wants to learn the basic concepts of Arduino and its operation in the field of robotics which is becoming increasingly important in our daily lives. In this learning kit, it provides three practical works that allow students to deepen their knowledge of the Arduino Uno microcontroller in robotics step by step. In Practical Work 1, students are exposed to the experiment of lighting three LED lights with pattern of running lights and flashing lights. In Practical Work 2, students are exposed to measurement work using ultrasonic detector and displaying its reading on a computer screen and on the screen of a mobile phone with the Android operating system via a Bluetooth module. In Practical Work 3, students are shown how to build a three -wheeled prototype robot and how to control the robot using a mobile phone with the Android operating system. The effectiveness of this learning kit has been tested in a learning workshop on 21 Pre-Diploma students of the Session of June 2020 Polytechnic of Sultan Mizan Zainal Abidin and has shown very encouraging feedback.